Light-induced hydrodynamic reorientation of hybrid aligned nematic liquid crystals caused by direct volume expansion. Issue 5 (9th April 2019) - Dadalyan, T.; Petrosyan, K.; Alaverdyan, R.; Hakobyan, R.
ABSTRACT: The dynamics of the direct volume expansion mechanism of light-induced hydrodynamic motions in hybrid-oriented nematic liquid crystal (NLC) have been studied experimentally. It was shown that heating caused by the absorption of a laser beam results in expansion of a NLC volume and induces hydrodynamic flow in a planar capillary. The hydrodynamic flow reorients the NLC molecules and thus the optical properties of the NLC layer are changing. A change of the tilt direction of the NLC director is demonstrated experimentally, and it is shown that hybrid-oriented NLC could be considered as 'flexible ribbon'. Velocity gradient brings about an increase of curvature when hydrodynamic flow velocity is directed out of the 'flexible ribbon's' curvature. The 'flexible ribbon' reverses its curvature when velocity is directed into 'flexible ribbon's' curvature. Graphical Abstract: